PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI TERHADAP PENERAPAN BUDAYA PATIENT SAFETY DI RS PKU MUHAMMADIYAH YOGYAKARTA UNIT II - Azuma, Anindita Paramastuti; Wahyuningsih, Roro Sri Handari; Alviana, Fifi (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2020)
Purpose: To analyzed the influence of the transformational leadership dimensions and both of partial and simultaneous motivation factors to the application of patient safety culture in the Hospital of PKU Muhammadiyah Yogyakarta Unit II. Methods: The purpose of this study waa analyzd the influence of the transformational leadership dimensions and both of partial and simultaneous motivation factors to the application of patient safety culture in the Hospital of PKU Muhammadiyah Yogyakarta Unit II. Results: The determination coefficient (R2) was 0.142. The F test shown that there was a positive and significant influence between transformational leadership dimensions and motivation factors to patient safety cultute with F=2.793 and p>0.05 (0.019) and the level of trust was 95%. Whereas idealized influence dimension (p<0.05=0.068) and motivator factor (p<0.05=0.001) were significant. Conclusion: Simultaneously, the transformational leadership dimensions and motivation factors influence the application of patient safety culture in the Hospital of PKU Muhammadiyah Yogyakarta Unit II.